TO THE QUESTION OF THE REPRESENTATION OF VASCULAR BASIN AS A SYMPTOM OF HYPERTENSION DISEASE - Марина Петровна Задорожная; Владимир Валентинович Разумов (Медицина в Кузбассе)
The pathophysiological problem of the study of the interaction of the heart and blood vessels in hypertensive disease is faced with the problem of choosing representative of both the vascular basin and its indices. For this purpose, a duplex duplex scanning of peripheral vessels of different calibers was performed in 154 patients (23 controls and 131 patients with arterial hypertension) with a study of their structural and functional parameters. A multilevel and heterogeneous vascular lesion was revealed at a given nosology, dictating, in scientific studies, the need to evaluate this «target organ» by bilateral research of as many vascular pools as possible. Remodeling of peripheral vessels revealed a tendency to asymmetry in arterial hypertension in all studied basins; The primary change in functional characteristics in the form of an increase in the speed of propagation of the pulse wave, a decrease in the diametrical expansion of the vessel with an increased vascular wall tension, and a reliable thickening of the artery wall of different caliber with a one-sided increase in the diameter of large arteries.